An Analysis of The President ‘S Speech - Rani Rakasiwi; Masriani Mery Rosmida Silalahi; Ricky Asi Erwindo Siahaan; Marlina Tampubolon (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
This study deals with Speech Acts used in the President Speech especially of the president of Jokowi's speech. The objectives of this research were to find out the types of Speech Acts used in Jokowi’s Speech. Descriptive qualitative method was applied in this study. After collecting the data, then the data was classified and analyzed based on the subcategories of Speech Acts acts. The results of this research shows The use of the types of Speech Acts in Jokowi’s Speech are Locutionary Acts with the total number of 17 speechs or 35.41 %; Illocutionary Acts with the total number of 17 speechs or 35.41 %; Perlocutionary Acts with the total number of 14 speechs or 29.18%.